Parental Social Support and Emotional Intelligence of Third-Year Junior High School Students - Muhammad Zulfa Alfaruqy (Jurnal Neo Konseling, 2023)
Emotional intelligence is the ability needed by junior high school students to answer the task of seeking identity development. It may be influenced by the social environment. This study aimed to examine the relationship between parental social support and emotional intelligence in students of SMP Negeri 1 Baturetno. From a total of 235 population, 170 students were obtained as participants using a simple random sampling technique. Data collection used the Parental Social Support Scale (12 items, α = 0.893) and the Emotional Intelligence Scale (11 items, α = 0.860). The results show that both parents' social support and emotional intelligence are in the high category. The analysis implies that there is a significant positive relationship between social support and emotional intelligence. The higher the social support, the higher the emotional intelligence. The correlation coefficient is categorized as moderate (r= 0.474) with a significance of 0.000 (p <0.05). Social support contributes to emotional intelligence by 22.5%. The research has implications for the urgency of a family as a social environment in adolescent development, including in the socio-emotional realm.